Drag Reduction of Wind Turbine Blade to Enhance Aerodynamic Performance: A CFD Study - Bisht, Priyanka; Sharma, Kanches (Journal of Graphic Era University, 2023)
The focus of the current majority of research efforts are focused on the investigation of passive flow control systems to provide wind turbine makers with efficient tools to increase the amount of energy that a wind turbine can use. In the current effort, our goal was to find a solution to enhance the HAWT blade aerofoil’s aerodynamic performance. Due to the ease of access to wind resources, wind energy is seen as one of the most significant energy alternatives for the future. From this, we may infer that multidisciplinary and necessary study in this area is required. This study aims to boost the operating capacity of wind turbines and their overall performance by performing full or partial flow attachment. The current work is focused on analyzing the flow around a wind turbine blade using CFD analysis. The current focus is on applying passive flow separation management to increase the aerodynamic efficiency of HAWT blades with S820 aerofoils.